Surface modification of poly(tetrafluoroethylene) and poly(ethylene terephthalate) films via environmental crazing. Issue 7 (14th March 2020) - Yarysheva, Alena; Strel'tsov, Dmitry; Malakhov, Sergey; Arzhakova, Olga; Yarysheva, Larisa; Volynskii, Alexandr
Abstract: This work addresses the phenomenon of the development of a patterned surface relief on polymer films via different modes of environmental crazing. Commercial films of semicrystalline poly(tetrafluoroethylene) (PTFE) and amorphous glassy poly(ethylene terephthalate) (PET) were subjected to tensile drawing in the presence of physically active liquid environments (carbon tetrachloride or aliphatic alcohols). The structure parameters and wettability of the modified films were studied by AFM, SEM, profilometer measurements and contact angle measurements. Environmental intercrystallite crazing of PTFE is accompanied by the development of an unstable structure with a high free surface, which experiences marked strain recovery upon unloading. As a result of the relief formation, PTFE hydrophobicity is enhanced (the water contact angle increases by 25°). Classical environmental crazing of PET films is accompanied by the formation of an anisotropic surface relief which is an assembly of crazes oriented perpendicular to the direction of tensile drawing, thus leading to the phenomenon of anisotropic wetting. The proposed approach for structural surface modification makes it possible to use the advantages of surface instability and spontaneous self‐organization of the polymer towards the development of a unique surface microrelief. © 2020 Society of Chemical Industry Abstract : Surface relief via environmental crazing of polymer